2016
DOI: 10.1002/ajcp.12098
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Homelessness among Emerging Adults Aging Out of Foster Care

Abstract: This study examines risk and protective factors associated with experiencing homelessness in the year after "aging out" of foster care. Using a state-level integrated administrative database, we identified 1,202 emerging adults in Washington State who exited foster care between July 2010 and June 2012. Initial bivariate analyses were conducted to assess the association between candidate predictive factors and an indicator of homelessness in a 12-month follow-up period. After deploying a stepwise regression pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 21 publications
3
56
0
Order By: Relevance
“…Homelessness stands as a salient indicator of hazards in this developmental transition that can significantly affect successful youth development as well as safety, adult role acquisition, and mental health. According to prior studies, approximately a quarter of youth aging out of foster care report being unsheltered for at least one day within the year of leaving foster care (Pecora, et al, 2005; Shah, et al, 2015), with 36% of youth having experienced homelessness at least once by age 26 (Dworsky, Napolitano, & Courtney, 2013). The results from this present study indicate that youth who have experienced more complex ACEs histories experience homelessness at a substantially higher rate than those with less complex ACEs histories.…”
Section: Discussionmentioning
confidence: 99%
“…Homelessness stands as a salient indicator of hazards in this developmental transition that can significantly affect successful youth development as well as safety, adult role acquisition, and mental health. According to prior studies, approximately a quarter of youth aging out of foster care report being unsheltered for at least one day within the year of leaving foster care (Pecora, et al, 2005; Shah, et al, 2015), with 36% of youth having experienced homelessness at least once by age 26 (Dworsky, Napolitano, & Courtney, 2013). The results from this present study indicate that youth who have experienced more complex ACEs histories experience homelessness at a substantially higher rate than those with less complex ACEs histories.…”
Section: Discussionmentioning
confidence: 99%
“…However, in doing so, important nuances of service use within each household type may have been lost. Other studies have highlighted important specialized concerns, risk factors, and vulnerabilities faced by families experiencing homelessness (e.g., Culhane et al., ; Shah et al., ; Shinn et al., ) versus single individuals experiencing homelessness. For example, Culhane, Metraux, Byrne, Stino and Bainbridge () have presented an interesting argument indicating that the cohort of individuals born between 1954 and 1961 in the U.S. has consistently been the most vulnerable to single person homelessness across time (1990–2010 in their study).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Shah et al. () have found that among those aging out of foster care, young adult parents were more vulnerable to episodes of homelessness than their non‐parent peers. That some of these nuances and concerns are blurred in the present study does represent a major limitation to the interpretation of these results.…”
Section: Discussionmentioning
confidence: 99%
“…In a representative sample of foster youth in California, over one-third of aged-out 19-year-olds experience homelessness and over 40% couch-surf (Courtney et al, 2016). An analysis of administrative data in Washington State finds more than one-quarter (28%) of youth experienced a homeless episode within 12 months of aging out of foster care; those who were African American, had experienced prior housing instability, or were parents faced the greatest risk (Shah et al, 2016). Similarly, a prospective study of aged-out youth from three Midwestern states (“The Midwest Study”) finds over 30% of aged-out young adults report episodes of living on the streets by age 26 (Dworsky et al, 2013).…”
Section: Introductionmentioning
confidence: 99%